Pengaruh Model Pembelajaran Team Assisted Individually dengan Crossword Puzzle Terhadap Minat Belajar Siswa Sekolah Dasar - Arief Rahman Hakim; Nury Yuniasih; Rosdianti Rosdianti (Jurnal Inspirasi Pendidikan, 2019)
This study aims to determine whether there is an influence of the Team Assisted Individually (TAI) learning model through crossword puzzles on student learning interests. This study uses a quantitative research approach with a Quasi Experimental Design research design with the Nonequivalent Control Group Design research design. The sample used was VA class students totaling 37 students as the experimental class and VB class totaling 38 students as the control class at SDN Bandungrejosari 3 Malang City. The instrument used was a questionnaire. Based on the results of hypothesis testing using the t-test with the help of the SPSS 16.0 program for windows, the ttable value was 1.666 and the tcount was 16.136. Sig value (2-tailed) of 0,000. Because the value of tcount > ttable (16,136 > 1,666) and significant 0,000 < 0,05, Ha is accepted and Ho is rejected, so it is concluded that there is a significant effect of the Team Assisted Individually (TAI) learning model through crossword puzzle on the learning interest of students in class V SDN Bandungrejosari 3 Malang City.